The Role of Türkiye in the “Solution” of the Question of the Sanjak of Alexandretta - Martirosyan, Arman (History and Culture, 2025)
The Middle East has been and still is considered for decades to be the most complex hub in the world, full of multi-layered contradictions, where intersect the interests of both the main actors of international relations and other regional countries. In this regard, it is particularly interesting to have an in-depth and comprehensive analysis of the features of Türkiye’s Middle Eastern policy in 1936-1939. In this context, the current paper is aimed at studying the motives and inducements of the Turkish authorities’ position towards the “solution” of the most sensitive issue in Turkish-Syrian relations, i.e., the ownership of the Sanjak of Alexandretta (İskenderun). Taking into account the geopolitical situation in Europe, both France and especially Great Britain gave great importance to Türkiye, and in order to neutralize the latter’s possible joining the German alliance, they went to the partition of Syria and “sacrificed” the Sanjak of Alexandretta to ensure the friendship and military alliance of Türkiye.